Early impact of the implementation of Medicaid episode‐based payment reforms in Arkansas. (21st May 2020) - Toth, Matt; Moore, Paul; Tant, Elizabeth; Rutledge, Regina; Beil, Heather; Arbes, Sam; West, Nathan; West, Suzanne L.
Abstract: Objective: To evaluate episode‐based payments for upper respiratory tract infections (URI) and perinatal care in Arkansas's Medicaid population. Study Setting: Upper respiratory infection and perinatal episodes among Medicaid‐covered individuals in Arkansas and comparison states from fiscal year (FY) 2011 to 2014. Study Design: Cross‐sectional observational analysis using a difference‐in‐difference design to examine outcomes associated with URI and perinatal episodes of care (EOC) from 2011 to 2014. Key dependent variables include antibiotic use, emergency department visits, physician visits, hospitalizations, readmission, and preventive screenings. Data Collection: Claims data from the Medicaid Analytic Extract for Arkansas, Mississippi, and Missouri from 2010 to 2014 with supplemental county‐level data from the Area Health Resource File (AHRF). Principal Findings: The URI EOC reduced the probability of antibiotic use (marginal effect [ME] = −1.8, 90% CI: −2.2, −1.4), physician visits (ME = 0.6, 90% CI: −0.8, −0.4), improved the probability of strep tests for children diagnosed with pharyngitis (ME = 9.4, 90% CI: 8.5, 10.3), but also increased the probability of an emergency department (ED) visit (ME = 0.1, 90% CI: 0.1, 0.2), relative to the comparison group. For perinatal EOCs, we found a reduced probability of an ED visit during pregnancy (ME = 0.1, 90% CI: −0.2, −0.0), an increased probability of screening for HIV (ME = 6.2, 90% CI: 4.0, 8.5), chlamydia (ME = 9.5, 90% CI: 7.2, 11.8), and group B strep‐test (ME = 2.6, 90% CI: 0.5, 4.6), relative to the comparison group. Predelivery and postpartum hospitalizations also increased (ME = 1.2, 90% CI: 0.4, 2.0; ME = 0.4, 90% CI: 0.0, 0.8, respectively), relative to the comparison group. Conclusion: Upper respiratory infection and perinatal EOCs for Arkansas Medicaid beneficiaries produced mixed results. Aligning shared savings with quality metrics and cost‐thresholds may help achieve quality targets and disincentivize over utilization within the EOC, but may also have unintended consequences.